Optimized resilience coupled with cost-effectiveness for grey and green infrastructure: a case study in a historical and cultural area, Guangzhou, China - Sun, Chuanhao (2025)
Coupled grey and green infrastructure (CGGI) is increasingly recognized as a viable approach to sustainable urban stormwater management. This study evaluates CGGI and grey infrastructure (GREI)-only schemes with various degree of centralization of the layout (DCL) in addressing urban flood and drainage issues in a historical and cultural district (HCD) which typically consists of high impervious surfaces, dense urban structures, and fragile heritage buildings. Yongqing Fang Community in Guangzhou, China, was selected as a case study in which the performance of the Grey-only and CGGI schemes are evaluated and compared. The results obtained indicated that the CGGI scheme was more advantageous in terms of cost-effectiveness and scalability, yielding potential savings of $30,500 to $163,400. Moreover, the fully decentralized layout of the two schemes could result in cost savings of 29.0% and 29.6%, respectively, over the fully centralized layout. However, CGGI shows marginally lower adaptability in response to extreme rainfall events compared to that of GREI-only solutions. Technical resilience (Tech-R) of GREI-only scored higher by 0.1% to 0.8%, 0.5% to 3.5%, and 0.7% to 4.8% for 10-year, 50-year, and 100-year rainfall scenarios, respectively. Nonetheless, CGGI schemes demonstrated superior adaptability in structural failure scenarios, and reduced surface overflow by 22.6%, 19.0%, and 18.4% compared to GREI for the same scenarios. In both the CGGI and GREI-only schemes, decentralized layouts are likely to outperform centralized layouts in both extreme rainfall events and in failure scenarios. These findings underscore the importance of decentralized layout of the drainage infrastructure which could enhance the hydrological performance of integrated drainage infrastructures, offering insights for due considerations in designing multi-objective infrastructures for urban flood mitigation in HCDs.